PENGOLAHAN AIR ASAM TAMBANG SECARA AKTIF DENGAN NETRALISASI MENGGUNAKAN KAPUR DAN NAOH (STUDI KASUS : WMP 18 SITE LATI, PT BERAU COAL) - Joaqim Mastroiani, Lalu
Acid mine water is not a new problem in the mining industry . Various attempts have been made to find the most optimum system in addressing the issue . Processing is applied can be either passive or active , active treatment can be carried out using a neutralization containing alkaline neutralizing agent . Lime is one of the neutralizing agent commonly used in treating acid mine drainage , but the material has a small solubility in water causes the processing system to be less optimal . Other materials that can be used as a neutralizing acid mine water is NaOH . This study was conducted to find the optimum dose of lime and NaOH to neutralize acid mine drainage in WMP 18 on Lati Site, Berau Coal . The research begin in the determination of the reference dose and then create variations of these doses to obtain the optimum dose . Monitoring is done by considering at the percentage of removal efficiency parameters of iron, manganese , and sulfate . The results showed that both neutralizing agent capable of removing up to 90 % iron , manganese allowance while in NaOH neutralizing agent has better efficiency by up to 75 % compared to the lime which has great efficiency up to 50 % .